Two unlikely bedfellows: Towards a decolonial unconference methodology - Gachago, Daniela; Hlatshwayo, Mlamuli; Nkoala, Sisanda; Van Heerden, Leanri (Critical Studies in Teaching and Learning, 2024)
This paper examines a specific unconferencing methodology designed for the HELTASA (un)conference, an international online event held in 2021 in South Africa. Drawing from the principles of unconferencing and decolonisation, the description of the unconferencing methodology in this paper is interspersed with collective autoethnographic reflections, collected through individual and collective writing engagements, to engage with our complex narratives as designers, facilitators and presenters/participants of this (Un)Conference. Through selected vignettes of reflective moments in planning and facilitating this (un)conference, we explore opportunities and challenges when adopting both principles of unconferencing and decolonisation in our practice. We end the paper with a discussion of the possibilities of adopting a decolonial unconferencing model in the global South through a colonial matrix of power.